Crisis Management Strategies in Jordanian Hotel Industry - ABO MURAD, Maisoon; AL-KHARABSHEH, Abdullah; AL-KHARABSHEH, Abdulrahman (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021DO - 10.14505//jemt.v12.2(50).27, 2021)
The aim of the current study is to identify the crisis management strategies in five-star hotels in Jordan. The most world wild crisis management strategies in hotel industry were synthesized from the literature. Data for this study were collected from 50 managers in five-star hotels in Amman. Self-administrated questionnaires were distributed to the targeted sample. SPSS was used to analyse the data and test the hypotheses. The findings showed that the strategies used to manage crises are coping and response strategies; furthermore, the most common strategy is the changing path strategy. This study offers some new insights about crisis management in Jordanian hotels. So, it aims to contribute to this growing area of research in developing countries.